Growblock: An Alternative Solution for Indoor Thermal and Visual Comfort Improvement - Wimala, Mia; Mandala, Ariani; Prastyatama, Budianastas; Yap, Yesaya Billy Surya Jaya; Elvira, (International Journal of Integrated Engineering, 2021)
The vertical garden offers an alternative to meet the needs of green space in a limited urban area with the upwards planting method. Its function, among others, includes improving air quality, insulating sound and heat, and thus, reducing energy consumption. Growblock, a result of previous research in 2018, combines the function of an interlocking wall block with a vertical garden planter in several design alternatives that can be used indoors or outdoors. This follow-up research will examine the potential of Growblock as an alternative strategy to support the practice of passive designs in buildings. Simulation using the Revit Insight Plugin was carried out to measure the amount of solar radiation received by the Growblock wall. The initial design will then be explored and evaluated by incorporating two other parameters that have not been developed before, i.e., openings for natural ventilation and daylights. The former will be calculated manually, while the latter will be simulated with the Velux Daylight Visualizer. The qualitative comparative methods from various similar literature were used in formulating modification alternatives design. The results were then be compared with the current standards for each parameter. Growblock was proven to reduce solar radiation by 53.03%, compared to conventional walls. This is due to the shade of the planters in Growblock which can protect the walls from direct exposure. Several design alternatives with various stack arrangements were also able to meet the requirements of openings for daylight of 1-5%, and for natural ventilation of more than 5% to the floor area. Do